Geestelijke verzorging als antropologisch laboratorium van postseculier Nederland - van den Hemel, Ernst (Religie & Samenleving, 2017)
This introduction to the special issue argues that the field of spiritual care is an indispensible support for people with increasingly pluriform spiritual needs. What is more, because of the continuous interaction between theory and practice, spiritual care can provide input and inspiration for academics and policymakers. As the papers in this special issue show, spiritual care works ‘on the ground’ with the many forms and meanings religion and spirituality take. Spiritual care, based on individuals’ identification and needs, can function as an anthropological laboratory, in which everyday experience is used as the starting point for thinking about the role of religion and spirituality instead of top-down categories and institutions. The experience of spiritual caregivers and the expertise collected in this special issue, provides a solution for a societal, academic and policy stalemate: how to engage with a pluriform spiritual society without depending too much on either the shapes of the (pillarized) past or resorting to secular indifference.